A randomized comparison of oral chloramphenicol versus ofloxacin in the treatment of uncomplicated typhoid fever in Laos - Simmaly Phongmany (2018)
We conducted a randomized open trial of oral chloramphenicol (50 mg/kg/ day in four divided doses for 14 days) versus ofloxacin (15 mg/kg/day in two divided doses for 3 days) in 50 adults with culture-confirmed uncomplicated typhoid fever in Vientiane, Laos. Patients had been ill for a median (range) of 8 (2-30) days. All Salmonella enterica serotype typhi isolates were nalidixic acid-sensitive, four (8%) were chloramphenicol-resistant and three (6%) were multidrug-resistant. Median (range) fever clearance times were 90 (24-224) hours in the chloramphenicol group and 54 (6-93) hours in the ofloxacin group (P < 0.001). One patient in the chloramphenicol group developed an ileal perforation. Three days ofloxacin was more effective than 14 days chloramphenicol for the in-patient treatment of typhoid fever, irrespective of antibiotic susceptibility, and was of similar cost. © 2004 Royal Society of Tropical Medicine and Hygiene. Published by Elsevier Ltd. All rights reserved.